Puisi Lisan Masyarakat Banda Eli Ketahanan Budaya di Maluku setelah Perang Pala - Timo Kaartinen (Antropologi Indonesia, 2012)
This article asks the question how Banda displaced from the Banda Islands due to colonization of Banda by the VOC in 1621, maintain their existence as a sustainable cultural group. Banda communities play an important role in maritime commerce in the eastern part of Indonesia at the beginning of the colonial period. They survive as one cultural group in two villages on the islands of Kei. The traditional songs of the two villages center on the sea voyage. The argument is that Banda people are mobilized by oral traditions that reveal the kinship ties of Banda people with their partners in commerce in distant lands. Key-words: oral poetry, Banda Eli Communities, cultural resistance